Morphological variation of the Scorpionfly Panorpa obtusa Cheng (Mecoptera: Panorpidae) with a new synonym. - Na Ma; Guilin Hu; Junxia Zhang; Baozhen Hua (PLoS ONE, 2014)
The overabundance of synonyms is an unavoidable by-product of taxonomic practice in insects. How to reduce or even eliminate synonymy has long been a great challenge for insect taxonomists. The scorpionflies Panorpa obtusa Cheng, 1949 and Panorpa leei Cheng, 1949 (Insecta: Mecoptera: Panorpidae) were originally described from Taibaishan in the Qinling Mountains with identical collection data and both are based on a single gender, the former on a male and the latter on two females. However, whether P. leei is conspecific with P. obtusa or a good species remains an unsolved problem.On the basis of intensive morphological comparison of 93 males and 53 females of scorpionflies collected from the type locality using light and scanning electron microscopy, we found P. obtusa has considerable morphological variation (especially the wing markings and genitalia in both male and female), and Panorpa leei is totally comprised of one of the morphs of P. obtusa.In combination with identical type localities and overlapping morphological variation, P. leei Cheng is proposed as a junior subjective synonym of P. obtusa Cheng. To avoid synonyms, taxonomists should pay more attention to individual variation and base decisions on a series of specimens to describe new species.